A study of chlamydial infection in pregnancy in Hospital Kota Bharu, Kelantan - Noor, Shah Reza Johan (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2005)
( .'h/amydia trachoma/is infection is the most common curable bacterial infection, and is now the most common sexually transmitted disease worldwide. World Health Organisation . fi gures estimated that 89 million new cases of geni tal chlamydia! infections· occur.rea;,'in 1995, highligh ting the worldwide prevalence of infections and the economic hurd.en .on hca rthcare delivery. For pregnant women, this infection has been associated with morbidity l()r both the mother and the newborn. Oh;ectives: This study was undertaken with th e objectives to detennine the prevalence of _ge nit<tl Chlamydia trachomatis inrection in pregnancy among the attendees of Antenatal Clinic of ll ospi tal Kota Bhant. Kelantan so as to ascenain ,,·hether universa l sc reen ing is needed or not. The other objective is to observe the c!Tccti vencss of treatment or chlamydia! infection with one-week course of erythromycin steartltc SOOmg qid . Methodology 44 0 pregnant women (age ran g~ 17 to 48 years old), in the li rst to thi rd ltllllester, attending the antenatal clinic of llospital Kota 11haru, Kelantan were tested for ( "/ilamydw trachoma fl s. Endocervical swabs were colkctcd fo r ( "hlamydia trac!Jo111ut1.\ diagnosis by Direct f- luorescence anti gen detection (DF A) technique. J?esu/ts: Out of 440 tested women, four were positive, giving the prevalence rate of 0.9%. No valid stati sti cal analysis can be made with regards to the age, gravidity, parity, socioeconomic status, education level, history of pr~maturity .or stillbirth or abortion between the positive and negative group because of ~he small number of wornen with positive results. All the four women with positive results were retested afler treatment and all of them were cleared. However, small numbt:;r of patients again, precludes further statistical analysis.